If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = -11 + -2k Solving 15 = -11 + -2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '2k' to each side of the equation. 15 + 2k = -11 + -2k + 2k Combine like terms: -2k + 2k = 0 15 + 2k = -11 + 0 15 + 2k = -11 Add '-15' to each side of the equation. 15 + -15 + 2k = -11 + -15 Combine like terms: 15 + -15 = 0 0 + 2k = -11 + -15 2k = -11 + -15 Combine like terms: -11 + -15 = -26 2k = -26 Divide each side by '2'. k = -13 Simplifying k = -13
| -0.6(6x-27)=-4 | | -3-9k=-21 | | 6-2p=29 | | -2x+4=-12-4x | | 16=-4n+3(-n+3) | | 25=.8(200-a) | | -5n+9=-21 | | 27=2p+12 | | 5x-8=-6+7x | | 22=8m+14 | | 20=.8(200-a) | | 10-n=7 | | 2x+7+3x=27 | | 9p+18=-45 | | 64=8(3x+5) | | 3m+21=15 | | 3n+4=34 | | -2x+5+7x=55 | | 4(p+6)=8p | | x^3-6X^2-x+30=0 | | 11r-2=24 | | 100-2n=60 | | -11-2=24 | | 3x-2=4x+6 | | 4x+7=3x+8 | | 3x+x+10=180 | | -6x-4=-64 | | m=21 | | -3x(x-4)-2x(x+3)= | | 2+x=-10 | | -52-3a=8 | | x+2y=27 |